2012
DOI: 10.1111/j.1752-1688.2012.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Contributions of Nitrate and Herbicides From Groundwater to Headwater Streams, Northern Atlantic Coastal Plain, United States1

Abstract: Groundwater transport often complicates understanding of surface-water contamination. We estimated the regional flux of nitrate and selected herbicides from groundwater to nontidal headwater streams of the Atlantic Coastal Plain (New Jersey through North Carolina) based on late-winter or spring base-flow samples from 174 streams. Sampled streams were selected randomly, and flux estimates are based on resulting population estimates rather than on empirical models, which have been used previously for similar est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 61 publications
1
33
0
Order By: Relevance
“…The USEPA's TMDLs require states and local governmental agencies to decrease or limit the total loads of contaminants to water bodies from both point and nonpoint sources to achieve water-quality standards (e.g., Delaware Department of Natural Resources and Environmental Control, 1998). Groundwater discharge is the primary source of N to streams on the Delmarva Peninsula, providing as much as 70% of the N flux, predominantly as nitrate (Ator and Denver, 2012;Domagalski et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The USEPA's TMDLs require states and local governmental agencies to decrease or limit the total loads of contaminants to water bodies from both point and nonpoint sources to achieve water-quality standards (e.g., Delaware Department of Natural Resources and Environmental Control, 1998). Groundwater discharge is the primary source of N to streams on the Delmarva Peninsula, providing as much as 70% of the N flux, predominantly as nitrate (Ator and Denver, 2012;Domagalski et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While field-based studies [Burns, 1998;Peterson et al, 2001;Duff et al, 2008;Mulholland et al, 2008Mulholland et al, , 2009Tank et al, 2008;Hall et al, 2009;Mulholland and Webster, 2010] and modeling approaches [Jaworski et al, 1992;Boynton et al, 1995;Alexander et al, 2000Alexander et al, , 2009Seitzinger et al, 2002;Boyer et al, 2006;Runkel, 2007;Ator and Denver, 2012] have provided much needed information on reach and watershed-scale nitrate dynamics, the limited spatial extent and/or low temporal resolution of discrete data collection continues to be a challenge for quantifying loads and interpreting drivers of change in watersheds. Recent studies have demonstrated that the collection and interpretation of high-frequency nitrate data collected using water quality sensors can be used to better quantify nitrate loads to sensitive stream and coastal environments [Ferrant et al, 2013;Bieroza et al, 2014;Pellerin et al, 2014], and provide insights into temporal nitrate dynamics that would otherwise be difficult to obtain using traditional field-based mass balance, solute injection, and/or isotopic tracer studies [Pellerin et al, 2009[Pellerin et al, , 2012Heffernan and Cohen, 2010;Sandford et al, 2013;Carey et al, 2014;Hensley et al, 2014Hensley et al, , 2015Outram et al, 2014;Crawford et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…For example, winter cover crops (WCCs) are recommended as a costeffective agricultural BMP for reducing nitrate loads (McCarty et al, 2008;Ator and Denver, 2012). Due to the high efficiency of WCCs in reducing nitrate loads, both Federal and state governments provide cost-sharing programs to encourage local farmers to adopt WCCs (McCarty et al, 2008).…”
mentioning
confidence: 99%